Can we teach publication competency? - Thaule, Jimi; Rundhovde, Tora (Septentrio Conference Series, 2023)
Watch VIDEO. Publication competency is a fundamental skill for researchers, serving as a vital criterion for attaining a Ph.D. degree. The European Qualifications Framework and Norwegian Qualifications Framework both recognize the importance of these skills. However, institutions differ in their approaches to teaching this skill set, with some neglecting it altogether. The specific skills required for researchers to publish their work extend beyond simply disseminating research appropriately. While the qualifications frameworks offer broad guidelines, various definitions, such as the Vancouver guidelines, the Norwegian NVI guidelines, and Plan S, need consideration. Specifically we have taken publication ethics, understanding impact, copyright and Open Access into consideration. In addition to benefiting Ph.D. students in their own endeavors, publication competency contributes to enhancing information literacy, research principles, and our local institutional knowledge. It establishes a foundation for a more systematic approach to teaching this essential skill. To address this issue, we conducted an analysis of Ph.D. students' competency levels in publication at the University of Agder, through interviews and questionnaires. Our findings align with previous research conducted at other institutions. In our forthcoming paper, we will discuss these findings and their implications for the University Library's approach to disseminating publication competency and creating robust institutional support systems, and suggest a method for increasing publication competency among Ph.D. students.